2012
DOI: 10.1177/0363546512439025
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Protects Bovine Articular Chondrocytes Against Cell Death Induced by Bupivacaine at Supraphysiologic Temperatures

Abstract: Background-Bupivacaine and supraphysiologic temperature can independently reduce cell viability of articular chondrocytes. In combination these two deleterious factors could further impair cell viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This precaution is further supported by a study of patients with damaged cartilage 38. A recent in vitro study has shown that hyaluronan can prevent chondrocyte death caused by bupivacaine at supraphysiological temperatures 39. However, whether coinjection of hyaluronan and bupivacaine intra-articularly may alleviate bupivacaine’s chondrotoxicity awaits further evidence from in vivo studies.…”
Section: Local Toxicitiesmentioning
confidence: 99%
“…This precaution is further supported by a study of patients with damaged cartilage 38. A recent in vitro study has shown that hyaluronan can prevent chondrocyte death caused by bupivacaine at supraphysiological temperatures 39. However, whether coinjection of hyaluronan and bupivacaine intra-articularly may alleviate bupivacaine’s chondrotoxicity awaits further evidence from in vivo studies.…”
Section: Local Toxicitiesmentioning
confidence: 99%
“…In osteoarthritis models, cartilage degeneration was reduced by HA [27,28]. Liu et al [19] reported that HA protected chondrocytes from death induced by bupivacaine at supraphysiologic temperatures. Grishko et al [29] reported that pretreatment of chondrocytes with HA can decrease mitochondrial DNA damage, preserve ATP levels, and increase cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular injection of hyaluronic acid (HA) has been widely used in the treatment of osteoarthritis [18] because it has chondroprotective and cytoprotective effects [19,20]. In addition, several animal studies have suggested that intra-articular injection of MSCs with HA is a feasible and promising minimally invasive method for cartilage repair [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Following joint fluid aspiration, 5 ml of 1% lidocaine were injected into the knee joint, and then 2.5 ml hyaluronic acid (Artz, Kaken seiyaku, Japan) were injected using a same needle. Because previous in vitro studies have shown that local anesthetics are chondrotoxic to human articular cartilage (Grishko et al 2010 ; Piper et al 2011 ), hyaluronic acid was added in expectation of protecting articular cartilage (Hester et al 2012 ; Liu et al 2012 ). The knee joint was passively moved from extension to flexion 5 times.…”
Section: Methodsmentioning
confidence: 99%